RETRACTED: Mechanisms of adipocyte regulation: Insights from HADHB gene modulation - Chaoyun Yang; Shuzhe Wang; Yunxia Qi; Yadong Jin; Ran Guan; Zengwen Huang (PLoS ONE, 2025)
The HADHB gene encodes the beta-subunit of 3-hydroxy acyl-CoA dehydrogenase, closely related to energy metabolism, fatty acid synthesis, and catabolism. This study aimed to investigate the effect of the HADHB gene on the proliferation and differentiation of bovine preadipocytes and to gain new insights into the mechanisms of adipocyte regulation. RNA was extracted from adipose tissue of yellow cattle and the HADHB gene CDS region was cloned. Meanwhile, isolation and cultivation of preadipocytes were used for siRNA and adenovirus overexpression, quantitative real-time PCR, transcriptome sequencing, and cell proliferation and cell cycle were measured by oil red staining, CCK8 assay, and flow cytometry. Subsequently, the transcriptome data were analyzed using bioinformatics. The results showed that the HADHB gene modulates significantly the expression of critical genes involved in proliferation ( CDK2 and PCNA ) and differentiation ( PPAR γ and CEBPα ), influencing preadipocyte proliferation and differentiation and altering cell cycle progression. The results of transcriptome sequencing demonstrated that the overexpression of the HADHB gene markedly altered the transcriptional profile of preadipocytes, with 170 genes exhibiting a significant increase in expression and 113 genes displaying a decrease. The HADHB gene exerts a regulatory influence on the differentiation process of precursor adipocytes by modulating the expression of key genes involved in proliferation and differentiation.These findings highlight the central role of the HADHB gene in adipocyte regulation and provide new insights into the regulatory mechanisms governing adipocyte biology.